Adoecimento dos docentes de pós-graduação stricto sensu: um estudo de caso : as influências da mercantilização do ensino superior neste adoecer - Lima Netto, Aristóteles Mesquita de (2020)
The present research, systematized and articulated in a thesis, fits in the line of Public Policies, State and Educational Institutions of the doctorate in education at the Pontifical Catholic University of Goiás (PUC-GO) with the thematic illness of stricto graduate teachers sensu in the state of goiás: the influences of the mercantilization of higher education in this illness, causing the precariousness of teaching activity as a product. The demand for issues to be worked on, developed and researched in school spaces in their relationship with illness becomes dense, the extreme relevance in the face of the illness of graduate teachers Stricto Sensu, for representing a still nebulous theme, in addition to involving educational policies contemporary, of the ultra neoliberalism economic model of the capitalist system, in force. Therefore, the health of the training professionals at the Stricto Sensu level is decisive for the advancement of science as a whole, of any nation, which is, mainly, with the commercialization operated at all levels of education in Brazil, specifically, in education programs. postgraduate studies. Based on this scenario, the research pointed out the following problem: how to know, interpret and analyze the relationship between the illness of Stricto Sensu graduate teachers at an HEI, in the state of Goiás, due to the imposition of the logic of increasing work productivity / greater exploitation / commercialization / precariousness of teaching activity? Therefore, the aforementioned research aims to: investigate the data, and consequent analyzes, raised by research in the context of the illness of these teachers, specific, through studies on dissertations and theses on the theme, carried out in the last 10 (ten) years, to analyze the illness situation of Stricto Sensu graduate teachers in education, in the state of Goiás, based on opinion questionnaires and document analysis, to relate the data collected by the bibliographic study, case study and document analysis, and the presence of the CAPES evaluation system in the Stricto Sensu graduate programs. This is a research of a dialectical character, more specifically guided by Marx (1986); (1987); (2013), Chauí (2013); (2019), Callegari (2019) and other theorists who portray the epistemological proposal in the historical perspective, authors and researchers in the scope of the commercialization of higher education, Freitag (1986), Silva (2009), Sguissardi (2006), Plastino (2007) , and in the context of illness, Bordalo (2013), Antunes and Praun (2015), Rodrigues (2009), among many others, became more frequent. This investigation is part of a case study. The first stage represented the bibliographic research, in the second stage we operationalized the documentary research, and in the third stage the opinion questionnaire was built. As a result, we point out the existence of a disease silenced in IES ¿C. Thus, the scenario raised in this case study coincides with the oppression resulting from the physical and emotional exhaustion experienced by postgraduate teachers in the last decades, which are responsible for or participants in the development of mental and physical illnesses. Thus, we highlight the relationship of neoliberalism as a market economy that enhances the levels of demand that erupt in the disastrous scenario experienced by the category of teachers in Brazil in the 21st century